(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This study examines the relationship between Digital Financial Services (DFS), Digital Literacy, and Financial Inclusion in Nigeria, focusing on how DFS adoption enhances access to financial services and promotes economic inclusion. In emerging economies like Nigeria, where many remain unbanked, DFS offers opportunities for broader financial participation. Digital literacy is identified as a key factor moderating the relationship between DFS and financial inclusion. The study employs a quantitative approach, using survey data from 300 respondents across Nigeria. Descriptive statistics, correlation analysis, and regression were applied for data analysis. The findings revealed that DFS adoption significantly improves financial inclusion, with users of mobile banking and e-wallets experiencing enhanced access to credit and payment services. Digital Literacy was found to positively moderate this relationship, as individuals with higher digital skills benefit more from DFS adoption. The regression analysis supports these results, with an R² of 0.63, demonstrating that 63% of the variation in financial inclusion outcomes is explained by the model. The study concluded that DFS and digital literacy are essential for promoting financial inclusion in Nigeria, recommending policy interventions to improve digital literacy, enhance digital infrastructure, and support DFS adoption through regulatory measures.